2006
DOI: 10.4067/s0717-95022006000500019
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Tendon and Tripartite Insertion Pattern of Fibularis Longus Muscle: A Case Report

Abstract: SUMMARY:The fibular muscles are the chief everters of foot and play an important role in stabilizing its subtalar motion. In the present case detected incidentally, we report a case of an accessory tendon and tripartite insertion pattern of fibularis longus muscle in the left leg, out of which two slips were attached to plantar and lateral aspects of base of first metatarsal and the third slip was found blending with first dorsal interosseous muscle. Awareness and precise knowledge of such anatomical variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…In another study, the tendon of fibularis longus muscle was dividing into two, where first inserted into the lateral side of base of first metatarsal & medial cuneiform and other into tuberosity of the fifth metatarsal bone [15]. Also, slip from the tendon of fibularis longus joining the first dorsal interosseous muscle has also been reported in the previous studies [15,13].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In another study, the tendon of fibularis longus muscle was dividing into two, where first inserted into the lateral side of base of first metatarsal & medial cuneiform and other into tuberosity of the fifth metatarsal bone [15]. Also, slip from the tendon of fibularis longus joining the first dorsal interosseous muscle has also been reported in the previous studies [15,13].…”
Section: Discussionmentioning
confidence: 77%
“…The insertion of the tendon designated as peroneo -peroneus longus has been mentioned, with its insertion to the fibularis longus muscle in sole [12]. Accessory tendon arising from fibularis longus muscle and joining back with its main tendon just proximal to lateral malleolus is described [13]. The insertion of fibularis longus muscle as three tendinous slips to fifth, third and first metatarsal bones with an occasional slip to intermediate cuneiform bone [11], an additional slip to the medial cuneiform in 86.6% and an additional band close to the metatarsocuneiform joint in 30% of specimens, has been described [14].…”
Section: Discussionmentioning
confidence: 99%
“…While the usual attachment is by a strong band to the base of the first metatarsal, there is usually an additional slip to the medial cuneiform. In a case report (Jayakumari et al 2006), the muscle was shown to have an accessory tendon and tripartite insertion. The accessory tendon attached to the base of the first metatarsal, and a tendinous slip inserted into the neighboring dorsal interosseous muscle.…”
Section: Discussionmentioning
confidence: 97%
“…Currently published literature encloses vivid data about variations in fibular group of muscles [6,[13][14][15]. Sobel et al conducted foetal study and classified AFM into two types -Type A (Fibularis quartus) and Type B (Fibulocalcaneus externus) [13].…”
Section: Phylogenetic Basismentioning
confidence: 99%